The Thinking Skills Deficit: What Role Does a Poetry Group Have in Developing Critical Thinking Skills for Adult Lifelong Learners in a Further Education Art College? - Frances Norton; Margaret Gregson (MDPI AG, 2020)
This article investigates Brown’s assertion that students today exhibit an unwillingness/inability to engage in critical thinking (CT). He describes this as a ‘critical thinking deficit’. The question of whether CT can be taught or whether we can only create the conditions in which CT can thrive and develop is explored through analysis of data from a pedagogical intervention of a Poetry Group; it aims to develop CT by employing Community of Inquiry as a methodology. This intervention was offered to a group of Further Education (FE) students over a period of six months with the intention of preparing them for progression into Higher Education (HE). Findings from the study lend support to the claim that sharing stories and poems is helpful in developing social and cultural capital across the group and in supporting CT and academic development. Students in the study report that they found the Poetry Group particularly valuable in encouraging both critical engagement with their Arts subject, deeper levels of learning and supporting improvements in attainment.